2003
DOI: 10.1159/000070091
|View full text |Cite
|
Sign up to set email alerts
|

A Psychological Cascade Model for Persisting Voice Problems in Teachers

Abstract: In 76 teachers with persisting voice problems, the maintaining factors and coping strategies were examined. Physical, functional, psychological and socioeconomic factors were assessed. A parallel was drawn to a psychological cascade model designed for patients with chronic back pain. The majority of the patients were found to be in a deadlocked situation (phase 1 of the cascade model), for which the combination of externalization and unawareness of the situation is the main risk factor. Subjective rating of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 22 publications
0
45
1
Order By: Relevance
“…A number of previous studies have also shown a positive relationship between voice disorders and various psychological problems [32][33][34][35][36][37] . However, because most of these studies used crosssectional designs, the causal relationship between the voice disorders and psychological conditions could not be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous studies have also shown a positive relationship between voice disorders and various psychological problems [32][33][34][35][36][37] . However, because most of these studies used crosssectional designs, the causal relationship between the voice disorders and psychological conditions could not be determined.…”
Section: Discussionmentioning
confidence: 99%
“…As voice disorders can adversely affect quality of life, they have been suggested as a cause of psychological symptoms such as stress, depression, and anxiety 32) . On the other hand, psychogenic factors might cause voice disorders by increasing tension in the laryngeal muscles, especially for muscle tension dysphonia [34][35][36] . A bidirectional relationship between psychogenic factors and voice disorders has also been proposed by other authors 33,35,37) .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence was not found that coping strategies have been the focus of prior research with people with SD. While coping styles have been explored in teachers with voice disorders (de Jong et al, 2003), caution should be exercised in extrapolating results from that study to the SD population because of different diagnoses and populations. Caution is also warranted in attempting to reconcile psychological coping profiles defined from the researchers' perspectives with the participants' interpretations of what it means to cope with a disability.…”
Section: My Personal Experience Of Sd-the Second Theme Of My Personalmentioning
confidence: 99%
“…Research about personality scales in relation to voice problems in teachers is a new area of study. There are reports that psycho-emotional factors are also associated with some voice problems [4,11,12,15,21,[26][27][28] . Certain studies have suggested that personality traits and psychological factors may even infl uence the ability of the voice to withstand a profession demanding on the voice [26,27,29,30] .…”
Section: Introductionmentioning
confidence: 99%
“…There are reports that psycho-emotional factors are also associated with some voice problems [4,11,12,15,21,[26][27][28] . Certain studies have suggested that personality traits and psychological factors may even infl uence the ability of the voice to withstand a profession demanding on the voice [26,27,29,30] . Personality has also been linked to important life outcomes [31][32][33] .…”
Section: Introductionmentioning
confidence: 99%